2022
DOI: 10.1126/scitranslmed.abe5795
|View full text |Cite
|
Sign up to set email alerts
|

The purinergic P2Y14 receptor links hepatocyte death to hepatic stellate cell activation and fibrogenesis in the liver

Abstract: Fibrosis contributes to ~45% of deaths in western countries. In chronic liver disease, fibrosis is a major factor determining outcomes, but efficient antifibrotic therapies are lacking. Although platelet-derived growth factor and transforming growth factor–β constitute key fibrogenic mediators, they do not account for the well-established link between cell death and fibrosis in the liver. Here, we hypothesized that damage-associated molecular patterns (DAMPs) may link epithelial cell death to fibrogenesis in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 74 publications
0
22
0
Order By: Relevance
“…Coherent with a potential increased usage of downstream-related metabolites such as UDP-Glc, depletion in early glycolytic intermediates (e.g., mannose-6-phosphate and glucose-6-phosphate) was observed in canonical UGT2B7 enzyme-expressing cells. Our findings further suggest that UGT enzymes may influence other cellular pathways in which UDP-sugars also participate, including the synthesis of the extracellular matrix component hyaluronan, protein glycosylation, and as ligands of the purinergic receptor P2Y14, which is involved in inflammation, asthma, fibrosis and acute kidney diseases [ 6 , 7 , 49 , 50 ].…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Coherent with a potential increased usage of downstream-related metabolites such as UDP-Glc, depletion in early glycolytic intermediates (e.g., mannose-6-phosphate and glucose-6-phosphate) was observed in canonical UGT2B7 enzyme-expressing cells. Our findings further suggest that UGT enzymes may influence other cellular pathways in which UDP-sugars also participate, including the synthesis of the extracellular matrix component hyaluronan, protein glycosylation, and as ligands of the purinergic receptor P2Y14, which is involved in inflammation, asthma, fibrosis and acute kidney diseases [ 6 , 7 , 49 , 50 ].…”
Section: Discussionmentioning
confidence: 78%
“…UGTs also regulate the bioavailability and activity of diverse endogenous metabolites including the product of heme catabolism bilirubin, sex steroid hormones, signaling lipids and serotonin [ 1 , 3 , 4 , 5 ]. For example, a number of receptors are activated by substrates of UGT enzymes, including sex steroids and prostaglandins [ 3 , 6 , 7 ]. These metabolites are involved in signal transduction pathways that control key transcription factors acting as major regulators of gene expression programs [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, dying hepatocytes also release damage-associated molecular patterns, such as P2Y14 ligands and the alarmin IL33, which activate mouse and human hepatic stellate cells through direct and indirect mechanisms and thereby promote fibrogenesis. 112 , 113 …”
Section: Role Of Hepatic Stellate Cells In Nonalcoholic Fatty Liver D...mentioning
confidence: 99%
“…19 Mederacke et al uncovered the purinergic receptor P2Y14 as highly enriched on HSCs and showed that the P2Y14 ligands UDP-glucose, UDP-galactose and UDP-glucuronic acid act as danger signals that are released upon liver injury and promote HSC activation and liver fibrosis. 48…”
Section: Key Pointsmentioning
confidence: 99%